Perspective Strategies for Finding New Means of Fighting with Infectious Diseases - B. G. Andryukov; T. S. Zaporozhets; N. N. Besednova (Антибиотики и Химиотерапия)
Increasing resistance of microorganisms to antibiotics has recently ceased to be an exclusively medical problem. It affects an ever wider range of socio-economic aspects of the world community and, having reached a high level, grows into a global threat to the health of the world's population. In the course of evolution, bacteria have developed a number of effective strategies for protection against antimicrobial agents. This causes the paramount importance of developing promising strategies for finding alternative strategies for combating infectious diseases. In this review, the authors discuss and analyze several areas of searching for new drugs, potentially capable of becoming an alternative to traditional antibiotic therapy.